2022
DOI: 10.3758/s13415-022-00989-y
|View full text |Cite
|
Sign up to set email alerts
|

The differential effects of brief environmental enrichment following social isolation in rats

Abstract: Environmental enrichment (EE) in rodents is associated with a wide range of physiological, affective, and cognitive benefits. A seemingly opposite housing condition, social isolation (SI), is used as a rodent model of stress, negatively affecting several neurobiological mechanisms and hampering cognitive performance. Experimental designs that involve switching between these housing conditions produced mixed results. We evaluated different behavioral and cognitive effects of brief EE following long-term, SI-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 136 publications
0
2
0
Order By: Relevance
“…laboratory animals demonstrated that EE resilience the SI induced impairment in working memory and reference memory [43,50,51], and spatial memory [29,43]. Specifically, EE resilience SI induced anxiety-like behaviour [52] and improve working memory in field-caught rodents [32,53].…”
Section: Plos Onementioning
confidence: 95%
See 1 more Smart Citation
“…laboratory animals demonstrated that EE resilience the SI induced impairment in working memory and reference memory [43,50,51], and spatial memory [29,43]. Specifically, EE resilience SI induced anxiety-like behaviour [52] and improve working memory in field-caught rodents [32,53].…”
Section: Plos Onementioning
confidence: 95%
“…On day 2, (i) Direct Wild (DW) group animals (n = 10) were subjected to hole-board test (HBT). Remaining animals (n = 35, 1/cage) were individually housed for social isolation (SI) in small standard laboratory cage (29.5×22×13cm) for ten days [43]. After the period of SI, animals were randomly divided into three groups: (ii) Short-Term at Standard Condition (STSC; n=10), housed at standard laboratory cage (43×27×15cm; 2-3/cage with Kleenex tissue paper as bedding) for seven days and then subjected to HBT; (iii) Long-Term at Standard Conditions (LTSC, n=10, 43×27×15cm; 2-3/cage with Kleenex tissue paper as bedding), which remained in the laboratory cage for another thirty days, then subjected to HBT.…”
Section: Experimental Group and Housing Conditionmentioning
confidence: 99%
“…Rapid-acting antidepressants, such as ketamine (Akan et al, 2023 ; Ecevitoglu et al, 2019 ; Kingir et al, 2023 ), replicated the antidepressant-like effect. Nonpharmacological antidepressant manipulations, such as environmental enrichment (Guven et al, 2022 ), also may produce therapeutic effects, providing further support for considering FST as a general test of antidepressant efficacy. Acute (Ünal et al, 2022 ) or chronic stress models (Kingir et al, 2023 ), in contrast, worsen behavioral despair in the FST by further increasing immobility compared with control groups.…”
Section: Depression-related Constructsmentioning
confidence: 99%
“…However, it does not explain how nonpharmacological antidepressant manipulations, such as environmental enrichment, prevents behavioral despair. Environmental enrichment has been shown to facilitate learning (Falkenberg et al, 1992 ; Guven et al, 2022 ; Schrijver et al, 2002 ); however, it often leads to a decrease in immobility in the FST. By restricting its argumentation to antidepressant drug use in the FST, the “coping strategy” interpretation found good support in the literature (Molendijk & de Kloet, 2019 ).…”
Section: Depression-related Constructsmentioning
confidence: 99%